Transport Reversal during Heteroexchange: A Kinetic Study. (26th October 2013) - Makarov, V.; Kucheryavykh, L.; Kucheryavykh, Y.; Rivera, A.; Eaton, M. J.; Skatchkov, S. N.; Inyushin, M.
Abstract : It is known that secondary transporters, which utilize transmembrane ionic gradients to drive their substrates up a concentration gradient, can reverse the uptake and instead release their substrates. Unfortunately, the Michaelis-Menten kinetic scheme, which is popular in transporter studies, does not include transporter reversal, and it completely neglects the possibility of equilibrium between the substrate concentrations on both sides of the membrane. We have developed a complex two-substrate kinetic model that includes transport reversal. This model allows us to construct analytical formulas allowing the calculation of a "heteroexchange" and "transacceleration" using standard Michaelis coefficients for respective substrates. This approach can help to understand how glial and other cells accumulate substrates without synthesis and are able to release such substrates and gliotransmitters.